High level of heterozygous haplotype of hemoglobin in Abidjan population with mild malaria - Tosséa A. Stéphane Koui; Alloh Albert Gnondjui; Adji Eric Gbessi; Ako Aristide Bérenger Ako; Baba Coulibaly; A. Delpêche Aka; Bi Sery E. Gonedele; Offiana André Toure; Ronan Jambou (BMC, 2022)
Abstract Background Sickle cell disease (SCD) is a hemoglobin disorders that concern 300,000 newborns each year around the world. There are hemoglobin haplotypes that affect SCD clinic expression. Methods Our goal was to identify the hemoglobin's haplotypes among individuals with mild malaria independently of SCD status in Côte d'Ivoire. To determine these haplotypes, specific restriction enzyme (RE) is used after PCR amplification with each primer. According to the digestion of PCR product by RE, five hemoglobin's haplotypes are found in the world. Results In Côte d'Ivoire, no study has yet deeply described the distribution of haplotypes. Four different "classical" haplotypes of hemoglobin were detected: Benin (56.5%), Bantou (28.5%), Senegal (4%), Cameroun (1%); and 10% of atypical profiles. Heterozygous haplotype (69%) were more frequent than homozygous haplotype (31%). Conclusions In this preliminary study, we note a high prevalence of atypical and heterozygous haplotype. Benin haplotype that is associated with severity of SCD was most predominant in our studied population.